Nutrition for post-exercise recovery - Burke, L. M. (Australian Journal of Science and Medicine in Sport, 1997)
Recovery after exercise poses an important challenge to the modern athlete. Important issues include restoration of liver and muscle glycogen stores, and the replacement of fluid and electrolytes lost in sweat. Rapid resynthesis of muscle glycogen stores is aided by the immediate intake of carbohydrate (I g.kg-1 BM each 2 hours), particularly of high glycemic index carbohydrate foods, leading to a total intake over 24 hours of 7-10 g.kg-1 BM. Provided adequate carbohydrate is consumed it appears that the frequency of intake, the form (liquid versus solid) and the presence of other macronutrients does not affect the rate of glycogen storage. Practical considerations, such as the availability and appetite appeal of foods or drinks, and gastrointestinal comfort may determine ideal carbohydrate choices and intake patterns. Rehydration requires a special fluid intake plan since thirst and voluntary intake will not provide for full restoration of sweat losses in the acute phase (0-6 hr) of recovery. Steps should be taken to ensure that a supply of palatable drinks is available after exercise. Sweetened drinks are generally preferred and can contribute towards achieving carbohydrate intake goals. Replacement of sodium lost in sweat is important in maximising the retention of ingested fluids. A sodium content of 50-90 mmol.L-1 may be necessary for optimal rehydration; however commercial sports drinks are formulated with a more moderate sodium content (10-25 mmol.L-1). It may be necessary to consume 150% of fluid losses to allow for complete fluid restoration. Caffeine and alcohol containing beverages are not ideal rehydration fluids since they promote an increased rate of diuresis.